Gods, men, and territory : society and culture in Kathmandu Valley - Vergati, Anne. (New Delhi : Centre de Sciences Humaines, 1995)
Social lifea and customs of Newars, Nepalese people from Nepal.
Includes bibliographical references and index.
Keywords: sociology; Kathmandu Valley (Nepal) -- Religious life and customs